Novel 4th-generation phytase improves broiler growth performance and reduces woody breast severity through modulation of muscle glucose uptake and metabolism - Walk, Carrie L.; Mullenix, Garrett J.; Maynard, Craig W.; Greene, Elisabeth S.; Maynard, Clay; Ward, Nelson; Dridi, Sami (Frontiers in Physiology, 2024)
The objective of the present study was to determine the effect of a novel phytase supplementation and its mode of action on growth, meat quality, and incidence of muscle myopathies. One-day old male broilers were weighed and randomly allocated to 30 floor pens with 10 replicate pens per treatment. Three diets were fed from hatch to d56: a 3-phase corn-soy based diet as a positive control (PC); a negative control (NC) formulated to be isocaloric and isonitrogenous to the PC and with a reduction in Ca and available P, respectively; and the NC supplemented with 2,000 phytase units per kg of diet (NC+P). At d56, birds fed with NC+P diet were significantly heavier and had 2.1- and 4.2-points better FCR compared to birds offered NC and PC diets, respectively. Processing data showed that phytase supplementation increased live weight, hot carcass without giblets, wings, tender, and skin-on drum and thigh compared to both NC and PC diets. Macroscopic scoring showed that birds fed the NC+P diet had lower woody breast severity compared to those fed the PC and NC diets, however there was no effect on white striping incidence and meat quality parameters (pH, drip loss, meat color). To delineate its mode of action, iSTAT showed that blood glucose concentrations were significantly lower in birds fed NC + P diet compared to those offered PC and NC diets, suggesting a better glucose uptake. Molecular analyses demonstrated that muscle expression of glucose transporter 1 (GLUT1) and glucokinase (GK) was significantly upregulated in birds fed NC+P diet compared to those fed the NC and PC diets. The expression of mitochondrial ATP synthase F0 subunit 8 (MT-ATP8) was significantly upregulated in NC+P compared to other groups, indicating intracellular ATP abundance. This was confirmed by the reduced level of phosphorylated-AMPKα1/2 at Thr172 site, upregulation of glycogen synthase (GYS1) gene and activation of mTOR-P70S6K pathway. This is the first report showing that supplementation of the novel phytase improves growth performance and reduces WB severity in broilers potentially through enhancement of glucose uptake, glycolysis, and intracellular ATP production, which used for muscle glycogenesis and protein synthesis.